TECHNOLOGY INNOVATION TO REALISE SUSTAINABLE AGRICULTURE - Mahidin Fahmie; Al-Amin (ADISAM Publisher, 2025)
Technological innovation plays a crucial role in achieving sustainable agriculture through advanced solutions that address challenges in the sector. The application of technologies such as Internet of Things (IoT), artificial intelligence (AI), and big data enables real-time monitoring of soil, weather, and crop conditions, which helps farmers in efficient resource management and smart decision-making. In addition, these technologies contribute to reducing environmental impacts by optimising the use of water, fertilisers and pesticides through precision farming practices. Nonetheless, challenges in technology adoption, such as high costs and lack of technical knowledge, remain. Collaboration between government, industry, and educational institutions is needed to provide financial support and training to farmers, so that technological innovations can generate sustainable benefits for the agricultural sector and society at large.